A BRIEF STUDY OF THE LIFE OF ASHRAFI OF SAMARKAND (American Journal of Research in Humanities and Social Sciences, 2022)
This article talks about the biography of one of the famous personalities, a powerful scientist, a philosopher, a good doctor, a connoisseur of the science of logic and astronomy and a poet of the 12th century Ashrafi Samarkandi. In particular, the name, surname, environment and literary activity of the poet are investigated in the article.